Scale regeneration in reared Gilthead seabream: Revisiting the use of scales in identifying aquaculture escapees. (16th April 2021) - Geladakis, George; Somarakis, Stylianos; Koumoundouros, Giorgos
Abstract: The high frequency of regenerated scales (degree of scale regeneration, SRD) in reared fish has been used in the past for the identification of aquaculture escapees in the wild stocks. In the present study, we examined the evolution of the SRD in Gilthead seabream ( Sparus aurata ) throughout the entire rearing process (hatchery and on‐growing, 2.0–21.9 cm standard length, SL). For this purpose, nine fish samples were randomly taken from different populations and farm sites, at different time points (58–393 days post‐hatching, dph). Results demonstrated that scales are lost continuously, from the onset of squamation (11.2 ± 5.7% mean SRD, 58 dph, 2.0 cm SL) to the end of the on‐growing period (98.7 ± 3%–99.8 ± 0.9% mean SRD, 314–393 dph, 21.7–21.9 cm SL). At the transition between the hatchery period and the on‐growing in sea cages, fish presented a wide distribution of SRD, ranging from 40% to 92% (122 dph, 5.1 cm SL). Despite the different sample origins, a uniform relationship between SRD and SL was observed, with a clear inflection point (2.7 cm SL) and two periods with different rates of scale loss. Our findings are discussed in relation to the use of regenerated scales for the identification of aquaculture escapees in wild stocks and the need to revisit the different suggested critical SRD thresholds.